Moving Beyond Diversity - Christopher Stuart Taylor; Grace A. Gomashie (Atlantis)
This paper argues that concrete actions are needed to address anti-Black racism and foster Black inclusion in Canadian higher education. These pertinent actions should target the systemic barriers faced by Black students when accessing post-secondary institutions. Through our reflections on current admissions practices of research-intensive Ontario-based universities, this paper highlights how currently used frameworks of diversity and inclusion may not be effective in disrupting the myth of meritocracy and mitigating systemic barriers faced by Black undergraduate applicants. We recommend that undergraduate admissions practices be grounded in a critical understanding of the four principles of the Scarborough Charter (Black flourishing, inclusive excellence, mutuality, and accountability) to support Black admissions, and that critical race theory and Black feminist thought be used as frameworks to create specific admissions practices and programs that disrupt anti-Black racism. The paper will generate further discussions on what it means to foster Black inclusion through university admissions and enrolment in a transformative manner.